1992
DOI: 10.1007/bf00213303
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal and metallothionein concentrations in Atlantic Canadian seabirds

Abstract: Seabird tissues, collected during the 1988 breeding season from colonies on the Atlantic coast of Canada, were analyzed for toxic metals--Cd, Hg and Pb--and 18 other trace elements. Metallothionein (MT) was measured in kidney, and kidneys and livers underwent histopathological examination. Levels of most essential trace elements appear to be closely regulated in seabird tissues; values were in good agreement with those previously reported in the published literature. Liver-Se concentrations in Leach's storm-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
73
6

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(96 citation statements)
references
References 60 publications
17
73
6
Order By: Relevance
“…Patchy necrosis were identified in kidneys of the seabirds accumulating 94.5-228 μg/g cadmium (Nicholson et al 1983), however this is not a rule (Eliott et al 1992). In adult Herring Gulls L. argentatus, collected in Atlantic coast of Canada, renal burden with cadmium ranged from 11 to 69 μg/g dry weight, but in the liver reached values ten times lower (Elliott et al, 1992). Our data are more comparable with the levels found in kidneys of the Puffin Fratercula arctica or Leach's Petrel Oceanodroma leucorhoa studied by the same authors (Elliott et al 1992).…”
Section: Toxic Consequences Of Metal Accumulation In Gullssupporting
confidence: 79%
See 1 more Smart Citation
“…Patchy necrosis were identified in kidneys of the seabirds accumulating 94.5-228 μg/g cadmium (Nicholson et al 1983), however this is not a rule (Eliott et al 1992). In adult Herring Gulls L. argentatus, collected in Atlantic coast of Canada, renal burden with cadmium ranged from 11 to 69 μg/g dry weight, but in the liver reached values ten times lower (Elliott et al, 1992). Our data are more comparable with the levels found in kidneys of the Puffin Fratercula arctica or Leach's Petrel Oceanodroma leucorhoa studied by the same authors (Elliott et al 1992).…”
Section: Toxic Consequences Of Metal Accumulation In Gullssupporting
confidence: 79%
“…In adult Herring Gulls L. argentatus, collected in Atlantic coast of Canada, renal burden with cadmium ranged from 11 to 69 μg/g dry weight, but in the liver reached values ten times lower (Elliott et al, 1992). Our data are more comparable with the levels found in kidneys of the Puffin Fratercula arctica or Leach's Petrel Oceanodroma leucorhoa studied by the same authors (Elliott et al 1992). The levels reported in our study also demonstrate that cadmium concentrations in the ovary were as high as in the kidneys, but expected reproductive abnormalities were not confirmed when we examined pathological changes in birds.…”
Section: Toxic Consequences Of Metal Accumulation In Gullsmentioning
confidence: 99%
“…In general, mercury, cadmium and lead are of primary concern in marine environments (Mailman, 1980;, they are non-essential, and are toxic (Elliott et al 1992). Each will be discussed below.…”
Section: Significance Of Levelsmentioning
confidence: 99%
“…Mattig et al 1997). Although previous studies found no clear patterns and associations of mercury levels with diets (Muirhead & Furness 1988, Elliott et al 1992b), recent studies on seabirds could relate mercury concentrations to the mercury burden of their prey (Monteiro et al 1995, 1996, Stewart et al 1999, Arcos et al 2002. Mercury is the heavy metal showing the clearest biomagnification in food chains (Honda et al 1987, Atwell et al 1998.…”
Section: Interspecific Variabilitymentioning
confidence: 99%